1D SnO2 with Wire‐in‐Tube Architectures for Highly Selective Electrochemical Reduction of CO2 to C1 Products. (28th February 2018) - Fan, Lei; Xia, Zheng; Xu, Meijia; Lu, Yingying; Li, Zhongjian
Abstract: Electrochemical reduction of CO2 (ERC) into useful products, such as formic acid and carbon monoxide, is a fascinating approach for CO2 fixation as well as energy storage. Sn‐based materials are attractive catalysts for highly selective ERC into C1 products (including HCOOH and CO), but still suffer from high overpotential, low current density, and poor stability. Here, One‐dimensional (1D) SnO2 with wire‐in‐tube (WIT) structure is synthesized and shows superior selectivity for C1 products. Using the WIT SnO2 as the ERC catalyst, very high Faradaic efficiency of C1 products (>90%) can be achieved at a wide potential range from −0.89 to −1.29 V versus RHE, thus substantially suppressing the hydrogen evolution reaction. The electrocatalyst also exhibits excellent long‐term stability. The improved catalytic activity of the WIT SnO2 over the commercial SnO2 nanoparticle indicates that higher surface area and large number of grain boundaries can effectively enhance the ERC activity. Synthesized via a facile and low‐cost electrospinning technology, the reduced WIT SnO2 can serve as a promising electrocatalyst for efficient CO2 to C1 products conversion. Abstract : In this work, a novel One‐dimensional (1D) SnO2 with wire‐in‐tube (WIT) structure is synthesized via a facile and low‐cost electrospinning technology for CO2 reduction. Superior selectivity for C1 products (>90%) is achieved at a wide potential range. This WIT SnO2 can serve as a promising electrocatalyst for efficient CO2 to C1 products conversion.